The impact of interventions addressing socioeconomic inequalities in cancer-related outcomes in high-income countries: A systematic review - Annie Bygrave; Kate Whittaker; Sanchia Aranda AM (SAGE Publishing, 2020)
Background: High cancer mortality is a major source of burden. Population-wide programs have been developed to improve cancer outcomes, and although effective in improving outcomes overall, the socioeconomically disadvantaged population have disproportionately benefited. This systematic review evaluated interventions aimed at addressing inequalities in cancer-related outcomes between low and high socioeconomic groups within high-income countries. Materials and Methods: The Cochrane Register of Controlled Trials, EMBASE, and PubMed searches were completed in October 2018. Data extraction and quality appraisal were guided by established mechanisms. Impact of interventions, using odds ratios, with respective 95% confidence intervals were presented, where available. Results: Sixteen studies reporting on 19 interventions were included. Seven interventions (37%) reduced socioeconomic inequalities in cancer-related outcomes, focusing on participation in cancer screening. Interventions included pre-formulated implementation intentions; GP-endorsed screening invitations; enhanced reminder letters; text message reminders; and implementation of an organised screening program. Conclusions: This systematic review found limited evidence on the efficacy of existing interventions that aimed to reduce inequalities in cancer-related outcomes between people living in low and high socioeconomic areas among high-income countries. Future interventions should consider the specific needs of people living in socioeconomically disadvantaged areas to improve the efficacy of an intervention.